Use of nanotechnology for clean and safer future environment - Guha, Dr. Pinaki (International Journal of Scientific Research and Management (IJSRM), 2017)
Nanotechnology is the most promising technology in modern science. This technology deals with the study and practical applications of different materials of nano-scale dimension. The chemical reactivity of a material increases immensely when we take its nano-dimensional form due to large surface to volume ratio and this special characteristic of a nanostructure is used widely in different environmental applications. Nanotechnology can be used in three different ways to tackle environmental pollutions. Firstly, we may use nanosensors to detect pollutant and pathogens in the environments. Secondly, we can apply nanotechnology for pollution remediation and treatment. Thirdly, nanotechnology may also be used as a tool to prevent our environment from further damage. Different nanowires and nanostructures are found to be very useful in detecting gaseous substances. Especially single walled carbon nanotubes (SWNT) are widely used for the detection of gases like NH3 , NO2 etc. The use of zero-valent iron (ZVI or Fe0 ) for in situ remedial treatment of soil and water has been expanded to include all different kinds of contaminants. Nanoparticles of TiO2 and ZnO are very effective in converting toxic contaminants of water by solar photo catalysis remediation. Nano-membrane and nano-filters have shown promise to produce pure drinking water and fresh air in future. Nanotechnolgy has a very bright future in the field of prevention and reduction pollution from our environment. Different nano-catalysts may reduce the use of toxic reagents and we can hope for a “Green Manufacturing” process in future.